2000
DOI: 10.1038/35037500
|View full text |Cite
|
Sign up to set email alerts
|

A mesoscale phytoplankton bloom in the polar Southern Ocean stimulated by iron fertilization

Abstract: Changes in iron supply to oceanic plankton are thought to have a significant effect on concentrations of atmospheric carbon dioxide by altering rates of carbon sequestration, a theory known as the 'iron hypothesis'. For this reason, it is important to understand the response of pelagic biota to increased iron supply. Here we report the results of a mesoscale iron fertilization experiment in the polar Southern Ocean, where the potential to sequester iron-elevated algal carbon is probably greatest. Increased iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
866
8
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,429 publications
(941 citation statements)
references
References 53 publications
39
866
8
10
Order By: Relevance
“…Because of logistical constraints, these experiments have been almost all shipboard bottle incubations (de Baar et al, 1990;Martin et al, 1990;Buma et al, 1991;Helbling et al, 1991;van Leeuwe et al, 1997;Olson et al, 2000) despite questions about bottleinduced changes in community composition and perturbation of grazing conditions (e.g., Banse, 1991). In situ enrichments, such as those carried out in the Equatorial Pacific (Martin et al, 1994;Coale et al, 1996) and more recently in the Southern Ocean (Boyd et al, 2000), overcome some of the limitations of bottle incubations, and their results have generally agreed with the findings from bottle incubations. Enrichment experiments, however, must be followed for days to document changes; in situ enrichments are especially complex logistically, and even shipboard experiments can be carried out only at selected stations.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Because of logistical constraints, these experiments have been almost all shipboard bottle incubations (de Baar et al, 1990;Martin et al, 1990;Buma et al, 1991;Helbling et al, 1991;van Leeuwe et al, 1997;Olson et al, 2000) despite questions about bottleinduced changes in community composition and perturbation of grazing conditions (e.g., Banse, 1991). In situ enrichments, such as those carried out in the Equatorial Pacific (Martin et al, 1994;Coale et al, 1996) and more recently in the Southern Ocean (Boyd et al, 2000), overcome some of the limitations of bottle incubations, and their results have generally agreed with the findings from bottle incubations. Enrichment experiments, however, must be followed for days to document changes; in situ enrichments are especially complex logistically, and even shipboard experiments can be carried out only at selected stations.…”
Section: Introductionsupporting
confidence: 68%
“…During in situ enrichment in the Equatorial Pacific (Kolber et al, 1994;Behrenfeld et al, 1996) and the Southern Ocean (Boyd et al, 2000), increases in chlorophyll a variable fluorescence were found to precede increases in chlorophyll concentration. Similar relatively rapid physiological responses can occur in bottle incubations with iron enrichment (Olson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, only the biologically active pool (defined here as bioavailable) is the fraction that can be effectively taken up by microorganisms to support their nutrient-dependent metabolic processes and growth (Hassler et al, 2012). Enrichment of Fe can drive shifts in the community structure from a nanoplankton (<10 m) to a microplankton (>10 m) dominated assemblage (De Baar et al, 2005), increasing the sinking of particulate organic carbon (POC) and thus export to the deep ocean (Boyd et al, 2000). As such, it is the bioavailable pool that shapes SO phytoplankton communities and caps the efficiency of the biological pump.…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%
“…There is now convincing evidence from Fe fertilization experi-ments to indicate that the low Fe concentrations found in HNLC areas are limiting phytoplankton growth (Martin et al 1991;Coale et al 1996;Boyd et al 2000). Despite the importance of bacteria for the carbon and nutrient budgets of the global ocean, bacterial growth limitation by iron in HNLC areas has not received so much attention as phytoplankton production.…”
mentioning
confidence: 99%